Peter Not-A-Rabbit: episode 42 happy Easter from the lilypad - Wurfel, Marlene (My University, 2018)
In Episode 42, Peter (who is not a rabbit) visits the Easter Bunny. Happy Easter from the Lilypad. An original story by Marlene Wurfel.
Keywords: storytelling; children's stories